Variable-rank imaging and testing of multi-frames for line array of ultrasonic guided waves with weld scattering - Xinjie ZHU; Yongtao LI; Mingxi DENG; Sen YAO; Jie ZHANG (Hanjie xuebao)
The imaging and testing of ultrasonic guided wave array in plates under the condition of weld scattering is of great significance. The variable-rank imaging of multi-frames for line arrays of ultrasonic shear horizontal( SH)guided waves is proposed for testing of weld plate. The imaging mechanism of variable-rank imaging of multi-frames for line array of ultrasonic guided waves with weld scattering is discussed, and the relationship between the receiving matrix and its rank is analyzed. The results show that when the weld scattering factor k ≥ 2, the rank of the receiving matrix will increase to (k-1) times the number of elements in the synthetic aperture array. With the increase of the rank of the receiving matrix, the defect grayscale and signal-to-noise ratio (SNR) of the variable-rank images of multi-frames increase to varying degrees. The SNR curves would have inflection points when the rank is half of the full rank, and the imaging effect would be better when the rank is two-thirds of the full rank. The variable-rank imaging of multi-frames for line array of ultrasonic guided waves would effectively characterize the defects with the same wavelength size in the weld plate. The imaging and testing of experiment verifies the effectiveness of the theoretical analysis, which demonstrate the feasibility and validity of this research approach.